Dynamic analysis of Magnetorheological Elastomer engine mount system - Ladipo, Ismail Ladele (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Passive, semi-active and active mounts have been used to isolate vibration in engines. However, due to changes in materials used for engine construction, there is a need to improve the performance of engine mounts. These improvements require sophisticated computation software, experimentation difficulties and cost. On the other hand, smart materials applications in engineering is growing but with lesser research on the analysis of models used for simulating behaviors of these smart materials. With proper analysis of mathematical models, isolation of engine vibrations can be improved in modern vehicles using smart materials. One of such smart materials is Magnetorheological Elastomer (MRE). Usually, dynamic responses of visco-elastic materials are observed using phenomenological experiments which include creep, stress relaxation and rheological models. The simulations of these dynamic responses and characterization of engine mounts using Magnetorheological Elastomers (MREs) are limited in literature. These have contributed largely to the absence of commercial MRE mounts albeit their characteristics and performance in theory. The aim is to develop characteristics equation for MREs and simulate its behavior as MRE mount. In this research, the comparison between the Standard Linear Solid (SLS) model and the MRE model reveals the mechanical properties of MREs. These mechanical properties are utilized in the simulation of dynamic behaviors of MRE mount. Sensitivity Analysis (SA) is then used to determine the importance of the parameters which contribute to the performance of MRE mount. The SA reveals that that magnetic field input is more important than characteristic constituents' stiffness of MREs. With this knowledge, MRE mount is controlled to reduce low frequency and high frequency vibration in half car model. It is shown by using different vibration measurement criteria, that there is significant reduction of vibration by using MRE mount. The results obtained when the Passive rubber mount was replaced with MRE mount shows 27% reduction in vibration in low frequency and 25% reduction in vibration in high frequency. The performance of the MRE in nonlinear model is however less promising as shown in the simulation results and further studies are needed. The values identified in this study can be useful in the subsequent design of MRE mounts in engine mount systems.